The Impact of COVID-19 Pandemic on Higher Education and Research: Learning from Experience and the Way Forward - Abdul Ghani, Ahmad Bashawir; Mahat, Nor Idayu; Omar, Mohd Faizal; Bakar, Shahbani Abu (Journal of Sustainability Perspectives, 2021)
The COVID-19 pandemic took its toll on many countries in early 2020 after the first case was reported in China at the end of 2019. Malaysia was not spared either and the Government was forced to take a bold yet drastic measure in implementing the Movement Control Order (MCO) in earnest on 18 March 2020. The measure, akin to a lockdown, practically forced all forms of socio-economics and socio-educational activities to come to an abrupt stop. Schools, institutions of higher learning and training centers were directed to close its doors to students. Universiti Utara Malaysia (UUM) had to abruptly implement contingency plans in the wake of the negative impact brought about by the pandemic. Almost all academic activities had to be reorganized when majority of the students opted to return to the safety of their home environment, and the staff were required to work from home in compliant with the MCO. This development necessitated the University to introduce the remote learning mode in place of the traditional face to face learning and teaching (T&L). Various other strategies and measures were also introduced by the University which required reprioritization of tasks and determining possible risks that could impede normal daily operations. UUM opted for a holistic approach to address the impending concerns and to ensure the continuity of the education process and to address the wellbeing of its staff who are forced to work from home.